Controversiality of the concept of absolute and the notion of creativity in Henryk Kamieński’s philosophy - Brzozowski, Tomasz Tadeusz (Folia Philosophica, 2010)
The paper is focused on interpretative analysis of the problematic construction of an absolute (absolutes) in Kamieński’s system, which is uncertain and controversial. Absolute as seen by Kamieński is not an absolute of all things (God) but a human being - „the absolute of all human things”. This makes the concept of Polish philosopher significantly different not only from other Polish thinkers but also from Hegel. According to Kamieński, man gets a knowledge concerning the existence of absolute form the absolute’s „results”. It cannot be recognized rationally. The recognition of the absolute in Hegelian sense could be possible only if the man would turn himself in God. Hence, an absolute a priori knowledge is possible in terms of human world only.